Kepailitan Suatu Solusi dalam Memaksimalkan Penagihan Piutang Kreditur (Lex Jurnalica, 2009)
The world recession often brought the impact on the business world. The bankruptcy was some resulting from the existence of this recession that happened because of the emergence of the dispute of the debt debt as a result of could not pay his debt. The bankruptcy was the solution to resolve this problem because the bankruptcy gave the assurance for the Creditor to regain his debt but also gave the protection to Debitor so that could divide in a pari manner the bowl to all Kreditornya.Keywords : Bankruptcy, Solution, Return of the Debt.